EFFECT OF MECHANICAL VIBRATION GENERATED IN OSCILLATING/VIBRATORY PLATFORM ON THE CONCENTRATION OF PLASMA BIOMARKERS AND ON THE WEIGHT IN RATS. - Ferreira Frederico, Éric Heleno Freire; de Sá-Caputo, Danúbia da Cunha; Moreira- Marconi, Eloá; Sampaio Guimarães, Carlos Alberto; Dionísio Cardoso, André Luiz Bandeira; Fontoura Dionello, Carla da; Morel, Danielle Soares; Sousa-Gonçalves, Cintia Renata; Paineiras-Domingos, Laisa Liana; Costa Cavalcanti, Rebeca Graça; Asad, Nasser Ribeiro; Marin, Pedro Jesus; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Whole body vibration (WBV) exercise has been used in health sciences. Authors have reported that changes on the concentration of plasma biomarkers could be associated with the WBV effects. The aim of this investigation is to assess the consequences of exposition of 25 Hz mechanical vibration generated in oscillating/vibratory platform (OVP) on the concentration of some plasma biomarkers and on the weight of rats. Materials and Methods: Wistar rats were divided into two groups. The animals of the Experimental Group (EG) were submitted to vibration (25 Hz) generated in an OVP with four bouts of 30 seconds with rest time of 60 seconds between the bouts. This procedure was performed daily for 12 days. The animals of the control group (CG) were not exposed to vibration. Results: Our findings show that the WBV exercise at 25 Hz was not capable to alter significantly (p<0.05) the weight of the rats. A significant alteration in the concentrations of amylase was found. Conclusion: Our results indicate a modulation of the WBV exercise with vibration of 25 Hz of frequency (i) in the pathways related to the weight and (ii) in the concentration of some biomarkers, such as amylase.